Order Picking: A Survey of Methods and Problems - Sinha, Sankalp; Kumar Nagda, Mayank; E. , Poovammal (International Journal of Psychosocial Rehabilitation, 2024)
Order picking is the single most expensive activity in warehouse management. Without tackling order picking successfully and efficiently it is almost impossible for any business to have a sustainable supply chain. Business around the world understand this and hence a lot of academic and research effort have gone into making the process of order picking as efficient as possible. Over the years many solutions have been devised and implemented. This paper presents a literary survey of the most used solutions and examines their salient limitations and problems faced during real world implementation.